Desulphurisation flotation for the selective removal of pyrite from coal discards using microorganisms - Msipa, Winfull Jaconia (Centre for Bioprocess Engineering Research, 2019)
Mineral beneficiation processes such as base metal and coal mining produce large amounts of waste rock and coal discards that contain significant quantities of sulphide minerals with Acid Rock Drainage (ARD) generating potential. ARD is caused by the exposure of sulphide minerals, primarily pyrite (FeS2), to both water and oxygen, and microorganisms. This is a naturally occurring process, but the exposure of the sulphide containing mining wastes greatly accelerates ARD formation. Thus, ARD is a major issue associated with inactive mines, waste rock dumps and tailings impoundments, which over time presents a major environmental risk. The desulphurisation of coal discards, mine tailings and finely divided waste rock prior to their disposal has been proposed as a method of preventing ARD formation. This involves the selective separation of residual values from the waste rock, followed by selective separation of sulphide minerals – especially pyrite – from the residual waste material using a two-stage froth flotation to obtain a values stream, a low volume sulphide-rich concentrate that can be easily contained, and a high volume benign tailings fraction that can be safely disposed of. The technical feasibility of this two-stage process has been demonstrated; however, the cost of the flotation reagents used in this process are particularly high in comparison to the other operating costs, contributing as much as 75% of the operating costs for desulphurisation of coal fines. Furthermore, apart from being expensive, many of the inorganic flotation reagents are relatively toxic and could be hazardous to the environment due to their slow degradation rate. Microorganisms and their metabolic products have been identified in literature as potential reagents that can be used in the selective separation of sulphide minerals using froth flotation. Just like conventional chemical flotation reagents, the microorganisms assist separation through surface chemical alterations that modify a mineral’s hydrophobic properties, thus facilitating bioflotation. The aim of this study was to investigate the prevention of ARD formation through the desulphurisation of pyrite-containing coal discards and base metal hard rock samples using microbial cultures as alternative bioflotation reagents. In this study the feasibility of using P. polymyxa, R. palustris, R. opacus, B. subtilis, and B. licheniformis as biocollectors for the removal of pyritic sulphur in the second stage of the two-stage desulphurisation froth flotation process was investigated. Microbial screening tests were performed using a pyrite concentrate to assess each microbial culture’s affinity to pyrite and their ability to float the mineral in a batch flotation cell. Attachment experiments and batch bioflotation tests were carried out to screen for a microbial culture that showed potential. Following attachment experiments at pH 4 and pH 7, all microorganisms except B. licheniformis exhibited attachment to pyrite. The level of attachment was different for each microbial culture. P. polymyxa had the highest percentage attachment of 95.6 ± 1.0 % at pH 4 and 97.1 ± 0.7 % at pH 7 after 20 minutes of interaction. Subsequent results from the pyrite-only bioflotation tests revealed that R. opacus, R. palustris and B. subtilis did not affect the floatability of pyrite. P. polymyxa, however, showed a significant effect on the floatability of pyrite, achieving a cumulative mass recovery of 7.0 ± 0.42 % at pH 4 and 81.3 ± 0.4 % at pH 7. Zeta-potential tests revealed that P. polymyxa had the most neutral net surface charge across the pH range tested, while the other microorganisms had a large net positive or negative charge. Based on this result, it was deduced that the hydrophobicity of P. polymyxa as a consequence of its near neutral surface strongly made it seek out a surface to attach to rather than remaining suspended in water. Hence, P. polymyxa was chosen as the bio-collector candidate for the bioflotation separation of pyritic sulphur from coal discard and base metal hard rock samples. Despite the positive batch pyrite bioflotation tests, P. polymyxa was not successful for the flotation of pyrite from the coal discards nor did it upgrade pyritic sulphur to the concentrate, with the bioflotation results not significantly different from the negative control without collector. P. polymyxa did affect the floatability of the base metal hard rock, achieving cumulative mass recoveries comparable with the chemical control using PAX. However, there was no significant upgrade of pyritic sulphur content, with the biofloat achieving 22.6 % total sulphur in the concentrate which was significantly less than the 66.4 % total sulphur recovered with PAX. The study thus yielded positive results from fundamental studies of P. polymyxa’s ability to enhance the flotability of pyrite. However, tests using actual samples were less successful. Although P. polymyxa enhanced the floatability of the base metal hard rock, it did not achieve the aim of obtaining a low volume sulphide-rich concentrate as the PAX did. Recommendations for the continuation of this work include contact angle measurements and FT-IR spectroscopy to better understand the effects of P. polymyxa attachment, as well as performing a kinetic study on the growth of P. polymyxa alongside adaptation of the microbial culture to a pyrite mineral concentrate in order to test if this can improve selective flotation of the desired mineral owing to modified surface properties.